Nanoparticle-assisted targeting of the tumour microenvironment - Tao Ming Sim (OpenNano, 2022)
Cancer collectively represents a major, debilitating source of global disease burden. While we are just beginning to unravel the mysteries behind the multifarious pathways and mechanisms underpinning the complex process of tumourigenesis, advances in tumour biology have led to our current appreciation of the tumour microenvironment (TME). The TME is a dynamic, bidirectional crosstalk between malignant cells and the surrounding microenvironment comprising acellular components such as the extracellular matrix and cellular components which include immune cells and endothelium. Mounting evidence suggests that the TME is instrumental in reprogramming crucial oncogenic processes such as tumour initiation, growth, cellular energetics, invasion and metastasis. Given the significance of the TME, cancer research revolving around a targeted, TME-centric approach to treatment has been gaining traction. Nanoparticle (NP) technology offers a platform for the design of tissue-specific carrier system owing to its versatile and modifiable properties. The prospect of NPs targeting specific cellular or acellular components of the TME offers technical advantages such as high precision of tissue-specific drug delivery and therefore minimizing deleterious systemic toxicity and side effects. This review spotlights the updated image of the TME and its role in tumourigenesis, with emphasis on the hypoxic niche, immune microenvironment, acidic niche and extracellular matrix, before a discussion of NP-based treatment strategies to target the various pillars of the TME.